Determinasi Kualitas Laba pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia - Masril, Masril; Safrizal, Safrizal; Arifin, Zahida Hasnul (Disclosure: Journal of Accounting and Finance, 2024)
Profit quality is a self-reflection for an organization in showing its performance to the public, so it is an important concern for stakeholders. This research aims to determine and analyze the influence of the audit committee, internal auditor and external auditor on earnings quality in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. This research is quantitative in the form of causality, meanwhile the type of data used is secondary in the form of company financial report data with the observation years 2018 to 2021. The population in this research is all manufacturing companies listed on the IDX, with a sample of 26 manufacturing companies in the goods industry sector. consumption, through purosive sampling techniques with companies in the consumer goods industry sector in 2018-2021 experiencing losses and being delisted. The results of this research show that the audit committee has an influence on the quality of company profits, while external auditors and internal audits do not have a significant effect on the quality of profits in manufacturing companies in the industrial sector. The contribution of this research states that research variables as a factor influencing the quality of company profits is only 10.6% and indicates that the contribution of research variables is still small in the research model used. The research implications reveal that it is important to increase the role of the audit committee and improve auditors in ensuring earnings quality.